IDENTIFICATION OF Escherichia coli BACTERIA IN DUG WELLS IN THE DISTRICT, EAST CITY OF GORONTALO: Doi: https://doi.org/10.47918/jhts.v3i1.334 - Syam S. Kumaji; Arpin; Daud, Srinianti U Daud (LP2M Universitas Bina Mandiri Gorontalo, 2021)
Well water is the main water source for providing clean water for people living in rural and urban areas. This well water is easily contaminated by disease-causing agents, especially Escherichia coli and other Colliform bacteria if the well is not made according to requirements.At a distance of less than 10 meters from the source of pollution, wells can be contaminated with human feces (feces) which contain bacteria, namely Escherichia coli, or the cause of water borne disease, namely diarrhea. Therefore, it is advisable to make a well at a distance of more than 10 meters so that the well is protected from various kinds of pollution that might seep into the well. Well spacing that does not meet health requirements makes it very possible to breed pathogenic bacteria that cause waterborne diseases.The purpose of this study was to identify Escherichia coli bacteria in dug wells owned by residents of Kota Timur District in Gorontalo. This research method uses cross sectionalwhere sampling is done one time at the same time. Examination by direct identification with growth on Nutrient Broth (NB) media, Eosin Methylene Blue Agar (EMBA), Sulfide Indol Motility (SIM), MR-VP, SCA and TSIA and gram staining to determine the presence or absence of Escherichia coli bacteria in water Dug wells. The results obtained from the fifteen samples that were examined did not show positive signs of Escherichia coli. It can be concluded that there was no dug well water that showed the presence of Escherichia coli, but found colonies of pink to purplish pink which were suspected of non-faecal coliform in dug well water in Kota Timur District of Gorontalo.